Ascertaining the Reality of Network Neutrality Violation in Backbone ISPs - Zhang, Ying; Mao, Z. Morley; Zhang, Ming (HotNets, 2008)
On the Internet today, a growing number of QoS sensitive network applications exist, such as VoIP, imposing more stringent requirements on ISPs besides the basic reachability assurance. Thus, the demand on ISPs for Service Level Agreements (SLAs) with better guarantees is increasing. However, despite over provisioning in core ISP networks, resource contention still exists leading to congestion and associated performance degradations. For example, residential broadband networks rate-limit or even block bandwidth intensive applications such as peer-to-peer ﬁle sharing there by violating network neutrality. In addition, trafﬁc associated with speciﬁc applications, such as Skype, could also bed is criminated against for competitive business reasons. So far, little work has been done regarding the existence of trafﬁc discrimination inside the core of the Internet. Due to the technical challenges and widespread impact, it seems somewhat inconceivable that ISPs are performing such ﬁne grained discrimination based on the application content. Our study is the ﬁrst to demonstrate evidence of network neutrality violations within backbone ISPs. We used a scalable and accurate monitoring system– NVLens – to detect trafﬁc discrimination based on various factors such as application types,previous-hop, and next-hop A Ses. We discuss the implication of such discrimination and how users can counter such unfair practices.